A Comparative Evaluation of Gutta-Percha and Sealer Removal of Rotary Niti File Retreatment Systems - Mirvet M. Rashad 1, Noor H. Fadhil 2, Raghad A. Al-Hashimi 3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Forty lower premolars with single root canals prepared with ProtaperNext files to size 25, and obturated with GP/sealer using lateral compaction. Teeth divided randomly into four groups (group n=10). Protaper universal retreatment kit (PUR), D-Race desobturation files (DRD), R-Endo retreatment kit (RE) and Hedstrom (H) files (control) were used to remove GP/sealer in each group. Removal effectiveness assessed by measuring the GP /sealer remnants in the roots after sectioning them into two halves. Stereomicroscope with a digital camera used to capture digital images. Images processed by ImageJ software to measure the percentage of GP/sealer remnants surface area in total, coronal, middle and apical areas of the canal. In the coronal area, PUR had significantly lower R% than RE and H groups, respectively (p<0.05). Also, DRD had significantly lower R% than RE (P<0.05). There was no significant difference between PUR and DRD (p>0.05), as well as no significant difference between RE and H groups(p>0.05). In the middle, apical and total root areas, Both PUR and DRD had significantly lower R% than RE and H groups, respectively (p<0.05). There was no significant difference between PUR and DRD (p>0.05). Also, there was no significant difference in R% between RE and H groups (p>0.05).